Step-by-step explanation:
Here we have , an expression c + 2 . We need to find that What happens to the value of the expression c+2 as c increases .Let's find out:
Let y = c + 2 or [tex]y = c+2[/tex] , where y is dependent on c and y is directly proportional to c i.e. as value pf c increase value of y increases . Let's have some example as
At c = 1
[tex]y = c+2[/tex]
⇒ [tex]y = c+2[/tex]
⇒ [tex]y = 1+2[/tex]
⇒ [tex]y = 3[/tex]
At c = 2
[tex]y = c+2[/tex]
⇒ [tex]y = c+2[/tex]
⇒ [tex]y = 2+2[/tex]
⇒ [tex]y = 4[/tex]
So , value of expression c+2 increases with value of c . Also , expression c+2 is a straight line having a slope of 1 and a y-intercept of 2 .